Canine visceral leishmaniasis: risk factors and spatial analysis in an endemic area of Northeastern Brazil - Samuel Souza Silva; Lucia Oliveira de Macedo; Jéssica Cardoso Pessoa de Oliveira; Leucio Câmara Alves; Gílcia Aparecida de Carvalho; Rafael Antonio Nascimento Ramos (Revista Brasileira de Parasitologia Veterinária, 2023)
Abstract Canine visceral leishmaniasis is a disease caused by the protozoon Leishmania infantum, an important agent of zoonotic concern. In this study we determined the seroprevalence, risk factors and spatial distribution of infection by L. infantum among dogs in the Pajeú microregion of the Sertão region of Pernambuco, Brazil. Canine serum samples (n = 247) were tested using the Dual Path Platform (DPP®) rapid screening test and ELISA/S7® confirmatory test; and risk factors were assessed through univariate analysis and logistical regression. The spatial distribution of reactive dogs was analyzed by drawing a map using QGIS. Seroprevalence of 13.7% (34/247) was detected, with cases predominating in the municipality of Tabira (26.4%; 9/34). Age above 10 years was considered to be a risk factor associated with the presence of anti-L. infantum antibodies. The high overall prevalence and spatial distribution of positive cases showed wide dispersion of reagents dogs in the study area. Therefore, preventive measures are needed in order to reduce the risk of infection for animals and humans.